Deep Learning Model CNN With LSTM For Speaker Recognition - Bassel Alkhatib; Mohammad Madian; Kamal Eddin (Journal of Digital Information Management, 2022)
Speech recognition is one of the most important research fields nowadays because of its necessity in our daily lives and to raise the fields of security to the highest level, It’s a task of speech processing, and our main scope in this paper is on speaker verification, which is to identify persons from their voices where the process depends on digitizing the sound waves into a form that allows the system to deal with it. The verification process is based on the characteristics of the speaker's voice (voice biometrics) and sends it to a further process to extract the features of that voice using the feature extraction method and using AI techniques to perform the task of identification. MFCC is used for the task of features extraction and obtains the spectrogram of a given voice signal where it represents a bank of information about the voice and sends it to the CNN model for further processing for training the model on that signal to verify if the voice belongs to a user in the system or it’s a new enrollment.

A Design of Chao Phraya Express Boat Route and Tourist Attraction Application On Android- - Hathairat Ketmaneechairat; Supakit Thurapan; Sireethorn Phadlom (Journal of Digital Information Management, 2022)
This paper aims to develop a design for the Chao Phraya Express Boat application and evaluate users' satisfaction with the Chao Phraya Express Boat application. In this paper, the Chao Phraya Express Boat application is developed to search the Chao Phraya Express Boat route, tourist attractions, and travel guide information. This application has been designed to present travel information, route map, timetable and emergency call. The results show that the users can search Chao Phraya Express Boat trip information using the pier's name or map. The application can display Chao Phraya Express Boat trip information such as the flag type, the distance between the starting point and the endpoint, timetable, transfer connection, fares and tourist attractions. The conclusion of the assessment of user satisfaction on the Chao Phraya Express Boat application for all the environments, the users have been highly satisfied.

Data Mining Applications for Banks’ Business Intelligence Maturity- - Mina Ranjbarfard; Shahideh Ahmadi (Journal of Digital Information Management, 2020)
There are many researches that applied data mining in banking. However, one may be countered the lack of suitable data as a serious obstacle to employ data mining techniques for the banks. This paper examines previous data mining researches carried out for banking, integrates them, extracts all served entities and attributes which are needed for analytical purposes, categorizes them and ultimately presents a suitable data model for analytical purpose. After analysis of a wide range of data mining application in banking, 28 entities with 423 attributes were identified in conclusion and the final proposed entity-relationship diagram was created. Also a checklist was provided based on the model for auditing data gap in banks and applied in a real case. The results of this paper can be regarded as a supportive tool for increasing banks’ business intelligence maturity from the data perspective and enable managers in requirement analysis of information systems.

Developing a Framework for Testing Android Applications based on Reverse Engineering Techniques- - Noor Jamal Alkhateeb; Mohammad Saeed AbouTrab (Journal of Digital Information Management, 2019)

Developing a Framework for Testing Android Applications based on Reverse Engineering Techniques- - Noor Jamal Alkhateeb; Mohammad Saeed AbouTrab (Journal of Digital Information Management, 2019)
It has been recognized that mobile platforms continue to prevail in all aspects of human activity. However, mobile applications might suffer from improper behavior just like other software types. Consequently, there is a growing need for testing mobile applications thoroughly. Model-based testing is one of the popular testing approaches, which depends on having a functional model of system specification to generate and evaluate test cases. In most cases, the specification model is not available, suffers from an unsatisfactory quality, or does not represent all business rules and functional requirements. That would lead to increase in the difficulties in testing, modifying and maintaining mobile applications. Reverse engineering can be used to reveal application’s designs, architecture and knowledge and extract models to represent them.

Data Fusion Techniques in Wireless Sensor Networks: Structured Vs. Structure-Free Approaches - Mahnaz Koupaee; Mohammad Reza (Journal of Networking Technology, 2018)

Data Quality Measures and Data Cleansing for Research Information Systems - Otmane Azeroual; Gunter Saake; Mohammad Abuosba (Journal of Digital Information Management, 2018)

Data Quality Measures and Data Cleansing for Research Information Systems- - Otmane Azeroual; Gunter Saake; Mohammad Abuosba (Journal of Digital Information Management, 2018)
The collection, transfer and integration of research information into different research information systems can result in different data errors that can have a variety of negative effects on data quality. In order to detect errors at an early stage and treat them efficiently, it is necessary to determine the clean-up measures and the new techniques of data cleansing for quality improvement in research institutions. Thereby an adequate and reliable basis for decision-making using an RIS is provided, and confidence in a given dataset increased.

Design and Development of Bi-Directional IoT Gateway using ZigBee and Wi-Fi Technologies with MQTT Protocol - Gopi Krishna Popuri; Srinivasa Ravi Kavuluri; Krishnaveni Kommuri (Journal of Electronic Systems, 2018)

Design and Development of IoT enabled Multi Robot System for Search and Rescue Mission - Rajesh Singh; Rohit Samkaria; Anita Gehlot; Sushabhan Choudhary (International Journal of Web Applications, 2018)

Developing Mobile Apps to Protect Environment - Iulia Georgiana Rinea; Delilah Florea; Adrian Florea (Journal of E-Technology, 2018)
The widely dependence on mobility has became nowadays a priority for people. The automotive industry has lately grown impressively a lot. Most of the people give cars an important place in ranking their priorities, and this is the reason of developing an Android application for mobile phone, to help resolve certain car problems, which often occur. This application is divided into three categories that facilitate the elimination of car damages. The first part is composed of symptoms, which users visual or auditory notice (observing a particular engine noise, unusual smoke detection). This part helps the car owner to repair the vehicle with only basic information in this domain. The second part is composed of a Google Map, which shows all the car services in a specific area. This part of the application is dedicated to serious problems of the vehicle, which cannot be detected and which can damage the car. The third part consists of connecting the phone to the onboard computer through a device OBD II ELM-327 Bluetooth that allows certain functions to appear on the mobile screen display (speed, air intake, fuel level). In conclusion, we believe that this application is useful, because it helps to clarify car key issues, contributing in this way also to solving the environmental problems regarding pollution.

Development of an Adaptive Collaborative Serious Game Based on Learning Style, Using Trace and Agent Technology- - Hadya Boufera; Fatima Bendella; Karim sehaba (Journal of Digital Information Management, 2018)
: In the collaborative serious game, adaptation is one of the main factors could be considered in the phase of conception since they can contribute to improve learning performance. Learning styles present one of the most factors that affect learning outcomes. Game-based learning (GBL) that takes into account learning styles in the process of adaptation, it furnishes to learners a greater benefit owing in the personalization of learning and contents materials according to their proper learning styles. cepted 6 January 2018 Journal of Digital Information Management DOI: 10.6025/jdim/2018/16/3/127-135 1. Introduction In this paper, Adaptive system that personalize a collaborative serious game based on learning style proposed by Felder and Silverman is described. This system used trace and agent technology. A model of trace and group model are developed to extract adaptation knowledge in order to form plan that will be executed by Npc player. To evaluate a system, an experiment has been conducted on group of students. From the experimental results, it is concluded that the adaptive collaborative serious game based on learning style improve learning outcomes and effectiveness, and promote learning motivation.

Development of an Adaptive Collaborative Serious Game Based on Learning Style, Using Trace and Agent Technology - Hadya Boufera; Fatima Bendella; Karim sehaba (Journal of Digital Information Management, 2018)

Development of an Integrated Model for Successful Adoption of Management Information Systems in Organizations - Yaser Al-Mamary; Murad Al-nashmi; Alina Shamsuddin; Yahya Abdul Ghaffar Hassan (Progress in Machines and Systems, 2018)

Dimensions of Changeability of Futuristic Organizations: Need of Organizations in Change Environment - Najme Jalalian; Masoud Gramipour (Journal of Data Processing, 2018)

Data visualization and retrieval based Convenience store location model of fresh products - Li, L. (Journal of Digital Information Management, 2017)

Design of access control system for hangul document system - Jang, S.J. (Journal of Digital Information Management, 2017)

The Design Research of Intelligent Suitcase- - Yongchuan Li (Journal of Digital Information Management, 2017)
By means of advanced mobile internet technology and combining with practical problem in use of suitcase, the smart suitcase is researched and developed to meet users’ demands for safety, carrying and entertainment, so as to provide users’ trip with intelligent solution. Meanwhile, the innovation of core functional units of smart suitcase is proposed to implement intelligent design of traditional suitcase, research suitcase relevant elements repeatedly, improve function, shape, structure, material, technology as well as color, and enhance product quality via design. On the one hand, the topic research refreshes traditional trip mode so that people can experience the convenience of smart trip; on the other hand, it provides people with faster use mode and meets users’ demands for personalized as well as high-tech products. Nowadays, the design of smart products under the era of internet of things has become a new trend, which meets users’ demand for suitcase, enables users to control smart suitcase easily with enjoying the comfort brought by the product, and keeps creating benefits for users and society.

The design research of intelligent suitcase - Li, Y. (Journal of Digital Information Management, 2017)

Dynamic parse approach of ladder diagram based on binary logic tree on the soft PLC system - Yang, G.; Yang, J.; Li, S. (Journal of Digital Information Management, 2017)

Dynamic tree based classification of Web Queries using B-tree and Simple Ordinal classification algorithm - Lakshmi, L.; Reddy, P.B.; Bindu, C.S. (Journal of Digital Information Management, 2017)

Data and text mining techniques for classifying Arabic tweet polarity - Brahimi, B.; Touahria, M.; Tari, A. (Journal of Digital Information Management, 2016)

Development of the method for integration of mobile applications and corporate information systems - Ptitsyn, P.S.; Radko, D.V.; Skrypnikov, A.V. (Journal of Digital Information Management, 2016)

Digital image clustering algorithm based on multi-agent center optimization - Pan, X.; Sagan, H. (Journal of Digital Information Management, 2016)

Digital Information Research Foundation: Editorial (Journal of Digital Information Management, 2016)

DVM-based topic detection for microblog - Lv, J.-G.; Jiang, X.-Y.; Chi, Q.-Y.; Wei, Z.; Jocshi, A. (Journal of Digital Information Management, 2016)

Denoising and segmentation of digital feather image using mean shift algorithm - Yue, H.; Cai, K.; Luo, B.; Jin, Y.; Zeng, Z. (Journal of Digital Information Management, 2015)

Differential evolution enhanced with composite population information based mutation operators - Liao, J.; Cai, Y.; Chen, Y.; Wang, T.; Tian, H. (Journal of Digital Information Management, 2015)

Digital audio resampling detection based on sparse representation classifier and periodicity of second derivative - Xu, J.; Xia, J. (Journal of Digital Information Management, 2015)

Do online recommendations matter? - A multimodal investigation of Amazon's co-purchase network - Chen, H.M. (Journal of Digital Information Management, 2015)

DTLS for lightweight secure data streaming in the Internet of Things - Fisher, R.; Hancke, G. (Journal of Digital Information Management, 2015)

DynMapNoCSIM: A dynamic mapping SIMULATOR for network on chip based MPSoC - Benhaoua, M.K.; Singh, A.K.; Benyamina, A.E.H.; Boulet, P. (Journal of Digital Information Management, 2015)

The design and implementation of library's user training system based on moodle - Sun, Y.; Liu, C.; Cui, X. (Journal of Digital Information Management, 2013)
A personalized online library user training system is built. Users can do self-training, group discussions, self-testing, personal views etc in the system. To make a friendly interface of the system, users will get interested in learning various retrieval skills and other resources. Taking the Library of Mudanjiang Medical University as the example, we build a user training system based on Moodle. The framework of the system consists of three parts: system module, resource module and activity modules. By using the system, users can more effectively improve the user's information retrieval ability, better use of library resources, especially databases; libraries can expand the scope of user training, and enhance the communication between the users and the libraries.
Keywords: Medical university library; Moodle; User training system

Design of a teaching robot based on fischertechnik model - Li, Z.; Huang, Z. (Journal of Digital Information Management, 2013)
This paper designed and developed a teaching robot - three degrees of freedom manipulator based on Fischer creative combination model platform. Firstly, the overall structure of the robot was analyzed to determine the drive programs, and then the manipulator structure was assembled and established in accordance with the modular design approach. Finally, the robot control system was studied. This paper focuses on the hardware design and control system of the robot. Practice has proved that the teaching robot we designed has the advantages of low cost, easy to regulation, good repeatability and it has good promotion and application prospects in the teaching field.
Keywords: Fischechnik model; PLC control system; Teaching robot

Differential evolution for rule extraction and its application in recognizing oil reservoir - Li, J.-L.; Guo, H.-X.; Zhu, K.-J.; Wang, D.-Y.; Hu, J.-L. (Journal of Digital Information Management, 2013)
The method of rule extraction based on differential evolution (DE-Rule) is proposed in this paper. The style of rule is IF-THEN. Connection word is AND in the antecedent of rule. The consequence of rule is class label. The above rule is encoded and expressed to individual in population of differential evolution. Then the population is iterated through differential mutation and binomial crossover. Optimal rule set is obtained after decoding the optimal individual. Finally, DE-Rule, RS-Rule and ANN-GA-Cascades-Rule are used to recognize oil reservoir (dry layer, water layer, inferiority layer and oil layer) in the Jianghan oil field. Data of well oilsk81 is training data and data of well oilsk83 is testing data. The results show that performance of accuracy and interpretability in DE-Rule is the best.
Keywords: Differential Evolution; Oil Reservoir; Rule Extraction

Digital information facial recognition based on PCA and its improved algorithm - Zhu, H.-F. (Journal of Digital Information Management, 2013)
Face recognition (PCA algorithm) based on principal component analysis method is a classic algorithm of digital information face recognition. This paper first analyzes the PCA algorithm and its basic principles. And in view of the shortage that it is affected by its subject facial expression changes and other factors, it designs the improved PCA algorithm, namely adding the image enhancement processing method, such as the local mean and standard deviation, to the original algorithm to increase the robustness of human face illumination and facial expression change during recognition. In addition, verify it on ORL face database and the results show that the improved PCA algorithm can get a higher resolution of the human face and up to 81.59% accuracy rate. The average growth of time-consuming is 0.378 seconds compared to traditional algorithms, and it is a fruitful improved algorithm.
Keywords: Digital information; Face recognition; Image enhancement processing method; Principal component analysis

A diversity-based multi-antenna cooperative detection model in cognitive radio network - Zhenquan, Q.; Wenjing, L.; Huizhen, J.; Weifeng, S. (Journal of Digital Information Management, 2013)
Spectrum sensing is a key technology in the study of cognitive radios, but its attributes are easily influenced by the channel fading. Compared with singleuser spectrum sensing, multiple-user spectrum sensing can overcome the impacts caused by the fading environment of cognitive radio. Since diversity technology has been proved to provide the system high transmission rate and high link reliability, we propose a diversity-based multi-antenna cooperative detection model based on the original cooperative detecting model. By introducing the antenna technology, sensing users are equipped with a multi-antenna system. Simulations show that the performance of our proposal is better than that of detection based on single-antenna in cognitive radio network. What's more, performance of cooperative detection based on multi-antenna is even better than that of cooperative detection based on single-antenna cognitive radio network.
Keywords: Cooperative detection; Diversity technique; Multi-antenna technology; Spectrum sensing

Duopoly game models of water supply in the presence of market power - Lu, H. (Journal of Digital Information Management, 2013)
The purpose of this paper is to investigate the allocation of output and the water supply for two firms to produce differentiated product in two oligopoly game models established under the settings of complete information and incomplete information respectively. By solving a linear demand system model, this paper obtains the corresponding allocation results of output and the water supply for two firms under the condition that the market power exists and the information on the marginal costs is complete. Furthermore, the relation between the allocation result of output and the equilibrium price of water markets in the framework of complete information is analyzed. The study result shows that when the equilibrium price of water markets raises, the total equilibrium output will decrease, while the change rule of the individual output is complicated. Under the condition that water consumption parameters in model are different, and the other parameters in model satisfy suitable conditions, the market shares of output due to the change of the equilibrium price of water markets transforms from the firm who requires more water quantity to the firm who requires less water quantity. Finally, this paper compares the allocation results obtained under the setting of incomplete information on marginal cost with that obtained under the setting of complete information on marginal cost.
Keywords: Oligopoly game; Strategic interaction; Water market; Water supply allocation

D3-P2P: Managing distributed and replicated database in P2P environment by using quorum system - Mounine, H.S.; Walid, H.K. (Journal of Digital Information Management, 2012)
The need for large-scale data sharing between autonomous and possibly heterogeneous decentralized systems on the Web led to the concept of P2P database systems. In this paper, we present D3- P2P a new architecture which allows to manage a distributed and replicated database, in Peer-To-Peer (P2P) system with high node dynamicity. This architecture is based on a quorum system to solve problems of concurrent update and nodes failure. The proposed architecture allows assigning a unique timestamp to each distributed transaction in order to build a local precedence order graph in each peer, to select the server replicas and to coordinate the distributed execution of the transaction. To avoid deadlock between nodes, we propose a fully distributed algorithm.
Keywords: Database; Deadlock; Failure; Node Dynamicity; P2P; Partial Replication; Quorum System

Design of the fuzzy intelligent controller of air compressor - Li, G.-F.; He, Y. (Journal of Digital Information Management, 2012)
The air compressor plays an extremely important role in the production of air separation. It provides the required specifications of compressed air for the follow-up air separation processes. It is difficult for an air compressor system to achieve the on-site production requirements because it is a time-varying, delay and nonlinear complex system. Articles for air compressor control system designed air compressor controller based on fuzzy control provided details of air compressor control strategies. The simulation experiments results showed that air compressor control requirements can be completed very well by controllers.
Keywords: Air compressor; Fuzzy intelligent control; Fuzzy pid controller; Pressure fuzzy controller; Time-varying system

Developing and deploying cloud services based on abstraction approach - Nguyen, B.M.; Tran, V.; Hluchy, L. (Journal of Digital Information Management, 2012)
With the advance of cloud computing, the trend of developing and deploying applications on cloud environment also has appeared recently. There are economic as well as technological reasons why an application should be developed and deployed on the cloud. Reducing costs and business agility are typical business factors for cloud-based applications. Cloud computing can provide significant cost savings because of the increased utilization resulting from the pooling of resources. In addition, this technology enables rapid delivery of IT services, which also improves business efficiency. On the operational side, manageability, performance, and scalability are the typical reasons why application developers consider cloud computing. However, cloud computing is still considerable complex to use. Not only the migration between clouds is difficult - but also the development and deployment of a new, complex service from the beginning could be quite a challenge using today's cloud computing. In this paper, novel high-level abstraction layers for cloud computing is presented. The abstraction layers will allow users to manage cloud resources form various clouds and simplify the process of developing and deploying services into those clouds. This approach will also solve absolutely the interoperability issue, thus improving the flexibility of cloud computing.
Keywords: Abstraction; Cloud computing; Cloud-based application; Interoperability; Object-oriented programming

The development and application of learning support service system for normal students' work placement - Shibo, Z.; Xuer, S. (Journal of Digital Information Management, 2012)
The model of normal students work placement has been a significant measure for the reform of teacher's education and with the development of distant education theory; thus the education model of networked learning activities arouses major concern. On the basis of new horizons of learning support service in this paper, it will start from three aspects which are the model of learning support service, the design of learning support service system and the application of learning support service accomplished in Work placement to provide an new and effective interactive model to normal students' work placement activities.
Keywords: Interactivit; Learning support service; System; Work-placement normal students

Distributed weighted clustering of evolving sensor data streams with noise - Hassani, M.; Seidl, T. (Journal of Digital Information Management, 2012)
Collecting data from sensor nodes is the ultimate goal of Wireless Sensor Networks. This is performed by transmitting the sensed measurements to some data collecting station. In sensor nodes, radio communication is the dominating consumer of the energy resources which are usually limited. Summarizing the sensed data internally on sensor nodes and sending only the summaries will considerably save energy. Clustering is an established data mining technique for grouping objects based on similarity. For sensor networks, k-center clustering aims at grouping sensor measurements in groups, each contains similar measurements. In this paper we propose a novel resource-aware -center clustering algorithm called: SenClu. Our algorithm immediately detects new trends in the drifting sensor data stream and follows them. SenClu powerfully uses a lightweighted decaying technique that gives lower influence to old data. As sensor data are usually noisy, our algorithm is also outlier-aware. In thorough experiments on drifting synthetic and real world data sets, we show that SenClu outperforms two state-of-the-art algorithms by producing higher clustering quality and following trends in the stream, while consuming nearly the same amount of energy.
Keywords: Algorithm; Data clustering; Data Processing; Wireless Sensor Nodes

The design and challenges of online reprogramming system for wireless sensor networks - Xie, M.; Zhang, G. (Journal of Digital Information Management, 2011)
At present, the online network reprogramming faces two challenges: 1) How to save the energy consumed during the code dissemination; and 2) How to enhance the security of online network reprogramming. In this paper, we modify the work flow of online reprogramming system and separates an alone reprogramming component from the whole program image which need not be transmitted in order to reduce the energy consumption. According to the security vulnerabilities in the image management aspects of code dissemination, acipher puzzle-based image management algorithm is proposed. According to the based-request attacks, several counter measures are introduced in our online reprogramming system, such as secure broadcast authentication based on cluster keys and the request count technique. By integrating several key techniques, our online reprogramming system can securely and energy-efficiently disseminate the new program image into the whole WSNs.
Keywords: Authentication; Hash Key Chain; Online Network Reprogramming; Wireless sensor networks

The design and implementation of the digital down converter based on the improved dds and dspbuilder techniques - Zhang, G.; Xie, M. (Journal of Digital Information Management, 2011)
DDC (Digital Down Converter), as a key part of digital receivers, aims to get low-speed digital baseband signals by extracting and filtering the digital signals transformed by high-speed ADC (Analog Digital Conversion). This paper employs the multi-rate process technique to design the DDC, i.e. firstly conducting data CIC (Cascade Integrator Comb) extraction, then HBF (Half-Band Filtering) and at last low pass filtering. CIC, which doesn't need multiplication, can realize high speed filtering and the HBF has high operation efficiency and good realtime performance. FPGA realization is taken into full consideration during the project design of the top. In the end, this paper adopts the Simulink instrument in MATLAB and combines Altera's signal processing toolbox-DSPBuilder to implement the design scheme by the FPGA. It focuses on the description of FPGA implementation of the digitally controlled oscillator, CIC filter, half-band extracting filter and the low pass filter.
Keywords: Digital Down Converter; Direct Digital Synthesizer; DSPBuilder

Detecting human sentiment from text using a proximity-based approach - Hasan, S.M.S.; Adjeroh, D.A. (Journal of Digital Information Management, 2011)
Sentiment analysis seeks to characterize opinionated or evaluative aspects of natural language text thus helping people to discover valuable information from large amounts of unstructured data. Sentiment analysis can be used for grouping search engine results, analyzing news content, reviews for books, movie, sports, blogs, web forums, etc. Several methods have been proposed for sentiment analysis at word, sentence, and document levels mostly based on common machine learning techniques. In this paper we explore a new methodology for sentiment analysis by considering a new set of features based on word proximities in a written text. We propose three proximity-based features, namely, proximity distribution, mutual information between proximity types, and proximity patterns. We applied this approach to the analysis of movie reviews, drug reviews, and music reviews. Our experimental results show that proximity-based sentiment analysis is able to extract sentiments from a specific domain, with performance comparable to the state-of-the-art. To the best of our knowledge, this is the first attempt at focusing on only proximity-based features as the primary cues in sentiment analysis.
Keywords: Machine learning; Movie reviews; Proximity analysis; Sentiment analysis; Text mining

A dynamic role-based authorization model in grid environment - Sun, W.; Guo, C.; Zhang, P.; Zhang, N.; Wang, H. (Journal of Digital Information Management, 2011)
In large-scale grid environment, the authorization plays a vital role in access control to resources. For the demand of higher dynamicity, complexity and granularity on grid environment, a novel model named dynamic role-based access control (DRBAC) based on RBAC model is presented. DRBAC introduces conceptions of several objects such as rolegraph initial structure, atom role and middle role, and it can automatically adjust the role-graph's structure through dynamically adding new roles or deleting original roles. The authorization mechanism which combines DRBAC model and CAS servers provides an effective method to solve loading and security problems. Theoretical analyses and example demonstrate that it is of high safety and has good time and space complexity when authorizing.
Keywords: CAS server; DRBAC; Dynamic role

A deadline-driven probabilistic quality of service routing for mobile ad hoc networks - Abbas, A.M.; Kure, Ø. (Journal of Digital Information Management, 2010)
Provision of quality of service (QoS) in an ad hoc network is a challenging task due to their inherent characteristics. In this paper, we present a routing protocol for QoS provisioning in mobile ad hoc networks. Our protocol tries to discover multiple node-disjoint paths between a given source and a destination that are able to satisfy QoS requirements in terms of bandwidth required by a fow of packets. We discuss how one can have probabilistic QoS guarantees using a protocol where nodes are aware of their neighbors that may interfere with them while relaying packets to other nodes along the paths towards the destination. We analyze the probability that the packets arrive at the destination before their respective deadlines.
Keywords: Nodedisjoint mulipath routing; Path independence; Probabilistic QoS guarantees; Quality of service

A dynamic load distribution algorithm for virtual worlds - Farooq, U.; Glauert, J. (Journal of Digital Information Management, 2010)
The introduction of modern communication and computation technologies has greatly changed the traditional approaches processing computationally intensive applications such as Virtual Environments (VEs). Distributed and multi-server architectures are scalable and exploit the concepts of spatial and temporal locality for handling massive Distributed VEs (DVEs). However, using these environments require special attention for scalability, consistency, load balancing, and latency. The existing mechanisms primarily developed for games have key performance issues in managing large scale virtual worlds. In our previous work (Farooq and Glauert, 2009a), we have proposed a hierarchical infrastructure named JoHNUM for the development of scalable and consistent virtual worlds. Further, we have introduced the concept of aggregate region assignment to minimise resource utilisation and distribute the load as balanced as possible among servers (Farooq and Glauert, 2009a, 2009b). This paper presents our proposed load distribution algorithm that yields regular and contiguous areas for assignment. It examines possible combinations of regions based on proposed strategies but greatly reduces the aggregation process by using different filters. It also presents a simple communication model justifying the proposed strategies and load distribution algorithm. Simulation results with an extended set of experiments show that the proposed algorithm obtains fair distribution of load and has the capability to cope with small, medium and large scale environments while minimising communication and implementation cost.
Keywords: Consistency; Load balancing; Scalability; Second life; Virtual Environment; Virtual world

Deriving the impact of scientific publications by mining citation opinion terms - Stamou, S.; Mpouloumpasis, N.; Kozanidis, L. (Journal of Digital Information Management, 2009)
One of the most important measures for estimating the impact of scientific publications is the number of citations they have received. To day, there exist several tools and metrics to evaluate the relative importance of individual papers and publication venues based on their citation distribution. Despite their acknowledged usefulness, most of the existing techniques rely on quantitative rather than qualitative aspects of the citation analysis and thus they are inherently limited in conveying any specific information about the author opinions to wards the papers they cite. In this paper, we introduce a method that combines text mining and lexical analysis in order to elucidate the authors' attitude towards the works they cite in their publications. We have applied our method on a set of 4,520 citations that span to 40 publications and tried to shed some light on the following issues. How often authors express an opinion about the papers they cite? Do all authors who cite the same publication share a common understanding on that publication's impact? Does the citations' context influence people's perception of the referred papers and how we can take context into consideration? Can we define a qualitative measure for esti mating the impact of scientific publications? Our evaluation shows that although authors do not always express their personal opinions about the papers they cite, their judgments (when articulated) have a great influence on the papers' perceived importance.
Keywords: Citation impact; Opinion mining; Sentiment analysis; Text mining

Design and development of a Query Graph Visualization system - Goh, D.H.-L.; Lee, C.S.; Chua, A.Y.K.; Luyt, B. (Journal of Digital Information Management, 2009)
Collaborative querying is a technique that harnesses the collective search experiences of users to assist in query formulation. We present the Query Graph Visualizer (QGV), a visual collaborative querying system that recommends related queries to a user's submitted query through a network visualization scheme. Users are able to explore the query network and select queries for execution on an information retrieval (IR) system. the QGV is not meant to be a replacement for IR systems but as a value-added module to help users search more effectively. Consequently, the QGV is not an IR system but works in tandem with existing IR systems. the design of the QGV is discussed, focusing on its architecture, the interaction between the QGV's main components and the implementation of the user interface. An evaluation of the QGV was also conducted to assess the performance of the system against to a conventional search engine. Results indicate that the evaluators who used the QGV completed their tasks much faster compared to those using a search engine alone. A usability evaluation also showed that the system complied with standard user interface heuristics.
Keywords: Collaborative querying; Information retrieval; Query Graph Visualize; Query network

Design and development of the dynamic DRBAC model using PMI and xacml-based authorization - Fugkeaw, S.; Manpanpanich, P.; Juntapremjitt, S. (Journal of Digital Information Management, 2009)
In the distributed computing environment, collaboration and resource sharing among several organizations are subjects of concern. Well-established authentication and authorization are thus vital. This paper proposes a novel design and implementation of Distributed RBAC (DRBAC) and Single Sign-On (SSO) system that spans over multiple administrative domains. Our key idea is based on Multi-Agent Systems (MAS) technique owing to its modularity, autonomy, distributedness, flexibility, and scalability. All agents serve their specific purposes. We use PKI technology to secure both intra- and interdomain agents communication as well as to establish trust relationships. The Security Assertion Markup Language (SAML) is adopted to support the exchange of authentication and authorization information in the architecture. The authorization scheme is based on the Privilege Management Infrastructure (PMI). In addition, we incorporate the XACML authorization concept into the MAS engine to support the relying parties or organizations whose their access control systems are written in XACML policy. Finally, we reported our extended implementation status and introduce the multi-instance processing technique to enhance the performance of the overall system.
Keywords: Drbac authorization; Privilege Management Infrastructure; SAML; X.509 public key certificate; XACML

Design and implementation of the Fast Send Protocol - Rabl, T.; Koch, C.; Hölbling, G.; Kosch, H. (Journal of Digital Information Management, 2009)
Over the last decades Internet traffic has grown dramatically. Besides the number of transfers, data sizes have risen as well. Traditional transfer protocols do not adapt to this evolution. Largescale computational applications running on expensive parallel computers produce large amounts of data which often have to be transferred to weaker machines at the clients' premises. As parallel computers are frequently charged by the minute, it is indispensable to minimize the transfer time after computation succeeded to keep down costs. Consequently, the economic focus lies on minimizing the time to move away all data from the parallel computer whereas the actual time to arrival remains less (but still) important. This paper describes the design and implementation of a new transfer protocol, the Fast Send Protocol (FSP), which employs striping to intermediate nodes in order to minimize sending time and to utilize the sender's resources to a high extent.
Keywords: Bulk-data transfer; Fast Send Protocol; FSP; FTP; GridFTP; High performance networking; Meridian; Striping; TCP tuning; Two staged transfer

Detecting phishing websites: On the effectiveness of users' tips - Alnajim, A.; Munro, M. (Journal of Digital Information Management, 2009)
Phishing attacks have become a serious problem for users of online banking and e-commerce websites. Many anti-Phishing approaches have been proposed to detect and prevent Phishing. One such approach is the anti-Phishing tips published by many governmental and private organizations to help users themselves to detect and prevent the attacks. This paper examines the effectiveness of the most common of the many different tips for detecting Phishing websites. A novel effectiveness criteria is proposed and used to examine each tip and to rank it based on its effectiveness score, thus revealing the most effective tips to enable users to detect Phishing attacks. Thus, proponents of anti-Phishing tips can focus on those tips which are most helpful to users in detecting Phishing attacks.
Keywords: Effectiveness; Internet fraud; Phishing; Phishing detection; Ranking

Distributed Web 2.0 crawling for ontology evolution - Juffinger, A.; Neidhart, T.; Granitzer, M.; Kern, R.; Weichselbraun, A.; Wohlgenannt, G.; Scharl, A. (Journal of Digital Information Management, 2009)
The World Wide Web as a social network reflects changes of interest in certain domains. It has been shown that free online content available through blogs, wikis, news media and online forums is a valuable source of information to identify trends in certain domains. Utilizing this data, one can construct ontologies that describe this information and provide a semantically correct overview of a domain. Tracked over time this also enables a user to identify trends and hypes. The decentralised structure of the Internet, the huge amount of data and upcoming Web2.0 technologies pose several challenges to a crawling system for ontology learning, evolution and trend analysis. This paper presents a distributed crawling system with browser integration for Web2.0. The proposed crawler is a high performance Web data retrieval system aimed to gather browser-equivalent textual Web content and prepare it for ontology learning.
Keywords: Distributed crawling; Executed crawling; Ontology evolution; Ontology learning; Web 2.0 crawling

Dual watermarking scheme for copyright protection and authentication - Bhatnagar, G.; Raman, B.; Swaminathan, K. (Journal of Digital Information Management, 2009)
Digital Watermarking is used for copyright protection and authentication of digital media-image/audio/video data. In this paper, a novel dual watermarking scheme is described based on Discrete Wavelet Transforms (DWT) and Singular Value Decompositions (SVD). Unlike the existing dual watermarking schemes, both the watermark embedded using DWT and SVD are invisible in the proposed scheme. For embedding, both the images are transformed into Wavelet domain and SVD is performed further on both the images. Subsequently the singular values are summed up to find the new set of singular values. Both the watermarks get embedded in the same manner. A reliable watermark extraction scheme has been developed for the extraction of the watermarks from the distorted image. Experimental evaluation demonstrates that the proposed scheme is capable of withstanding variety of attacks.
Keywords: Digital dual watermarking; Gray-scale logo; Multiresolution analysis; Singular Value Decomposition; Wavelet Transform; Zig-zag sequence

Discriminant parallel feature fusion based on maximum margin criterion for pattern classification - Li, J.-B.; Chu, S.-C.; Pan, J.-S. (Journal of Digital Information Management, 2008)
In this paper, we propose a novel parallel feature fusion based maximum margin criterion, namely discriminant parallel feature fusion, for pattern classification. The advantage of algorithm lies in: 1) A constrained optimization problem based on maximum margin criterion is created to solve the optimal fusion coefficients, which causes that fused data has the largest class discriminant in the fused feature space. 2) An unique solution of optimization problem is transformed to an eigenvalue problem, which causes the proposed fusion strategy to perform a consistent performance. Besides of the detailed theory derivation, many experimental evaluations also are presented in this paper.
Keywords: Discriminant parallel feature fusion; Maximum margin criterion; Parallel feature fusion

Digitized information management: The dynamic information system - Halonen, R. (Journal of Digital Information Management, 2007)
This research focuses on the change process that led to a digitized information system in academia. The development was carried out in a project where the participants represented their universities. The biggest issue to manage was to define the electronic process that was to be coded to support student mobility between universities. Action research was chosen as the research method because of the strong involvement of the researcher in the case. The output was evaluated satisfied, even excellent by the users and the goal was achieved despite minor knowledge about designing information systems in the project group.
Keywords: Change process; Digitizing; Interorganizational information system; User participation

Domain knowledge based queries for multimedia data retrieval - Hammiche, S.; Lopez, B.; Benbernou, S.; Hacid, M.-S.; Vakali, A. (Journal of Digital Information Management, 2007)
This paper describes an approach for semantic description and retrieval of multimedia data described by means of MPEG-7. This standard uses XML schema to define the descriptions. Therefore, it lacks ability to represent the data semantics in a formal and concise way and it does not allow integration and use of domain specific knowledge. Moreover, inference mechanisms are not provided and hence the extraction of implicit information is not (always) possible. To address these issues, we propose to add a conceptual layer on top of MPEG-7 metadata layer, where the domain knowledge is represented using a formal language. A set of mapping rules is proposed. They serve as a bridge between the two layers. Querying MPEG-7 descriptions using XML query languages such as XPath or XQuery requires to know MPEG-7 syntax and documents structure. To provide a flexible query formulation, we exploit the conceptual layer vocabulary to express user queries. A user query, making reference to terms specified at the conceptual level, is rewritten into an XQuery expression over MPEG-7 descriptions.
Keywords: Logic languages; Mapping rules; MEPG-7; Multimedia data descriptions; Ontology; Semantic and structural aspects

The designing of web services to deliver web documents associated with historical links - Chao, D.; Gill, S. (Journal of Digital Information Management, 2006)
The historical links of a web site include the URLs invalidated due to web site reorganization, document removal, renaming or relocation, or links to document snapshots, which are defined as the document's contents as of a specific point in time. Tracking historical links will allow users to use out-of-date URLs, retrieve removed documents and document snapshots. This paper presents a logging and archiving scheme to track a source document's history of changes, and designs web services to deliver the source document associated with a historical link.
Keywords: Concept mapping; Hyper space; Information extraction; Knowledge discovery; Semantic web; Web knowledge discovery; Web navigation

A dynamic priority allocation scheme of messages for differentiated web services satisfying service level agreement - Kim, D.; Lee, S.; Abraham, A.; Han, S. (Journal of Digital Information Management, 2006)
Recently many enterprises are adopting web services as the standard between heterogeneous software in the XML message based distributed environment to carry out businesses from B2C to B2B. For effective application of web services, differentiated service quality must be guaranteed. However, majority of the current web services do not differentiate quality of messages and the current web servers do not reflect the quality factors of the service level agreement settled between the service provider and user. Our research analyzes the appropriate quality factor for the quality level where differentiated service is provided and suggests a method for assigning priorities to web service message processing processes based on these quality factors. The suggested method assigns the priority dynamically in order to satisfy the service level agreement as much as possible.
Keywords: B2B; B2C; Web servers; Web service; Web service quality